Landscape, atmosphere and the sky (Lebenswelt. Aesthetics and philosophy of experience., 2024)
This essay traces the evolution of my thinking from ecological anthropology to a synthesis of linealogy and meteorology. As my ideas developed, via concepts of landscape and taskscape, I began to think of human lives as lived along lines, entangled in a meshwork. Yet every life is also lived on the ground, in the zone of interpenetration between earth and sky. And the sky is the domain of the weather. My challenge was then to understand the relations between lines and the weather, or between the meshwork and the earth-sky world. This is where the atmosphere came in. Through a critique of the aesthetics of atmosphere, I argue for an approach that, in reintroducing the element of air, would fuse cosmos and affect. But this means undoing the inversion, characteristic of modernity, which turns the earth-sky world into landscape and scenery on which life is enacted. Ultimately, I find the relation between lines and the weather in the alternation of breathing in and breathing out.